Genotoxicity study of sea coral used as bone replacement material - Hamid, Suzina Sheikh Ab; Samsudin, Ab. Rani; Omar, Nor Shamsuria; Ahmad, Azlina
Most of the methods available today to detect carcinogens and mutagens are based upon the principle that genotoxicity/mutagenicity may serve as an indicator of carcinogenic potential.This in vitro study was made to evaluate the genotoxicity characteristic of coral of Porites sp. produced by the National Tissue Bank, Universiti Sains Malaysia (USM), by using the Bacterial Reverse Mutation Assay test or Ames test.The Bacterial Reverse Mutation Assay of the coral material was performed on Salmonella typhimurium strains TA98, TAIOO, TA1535, TA1537 and Escherichia coli strain WP2 uvr A using the preincubation method in the presence and absence of an exogenous metabolic activation system. The results showed the numbers of revertant colonies of all strains which -were treated with the test substance were less than twice that of each negative control with and without S9 Mix.In conclusion the results of the tests showed that the coral material was considered to have no reverse mutagenic potential under the present test condition.